2011
DOI: 10.1080/07370016.2011.539087
|View full text |Cite
|
Sign up to set email alerts
|

Using the Health Belief Model to Understand Caregiver Factors Influencing Childhood Influenza Vaccinations

Abstract: The survey results can be used to develop strategies for increasing influenza vaccination rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
119
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(141 citation statements)
references
References 29 publications
(52 reference statements)
14
119
2
1
Order By: Relevance
“…Related to the Singapore research locus, one strength of this study in its non-US research locus that provides further evidence of cross-cultural validation of the HBM, which in this study has demonstrated its predictive utility consistent with other HBM studies, especially that focusing on parental roles. 10,21,25,26 The HBM has proved to be an efficient tool in predicting health behaviors based on health beliefs. Consistent with other studies on dietary and health actions of parents, 21,39 in this study, perceived susceptibility, perceived severity, and cues to actions are significant predictors of health actions toward children's fast food consumption to prevent childhood obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to the Singapore research locus, one strength of this study in its non-US research locus that provides further evidence of cross-cultural validation of the HBM, which in this study has demonstrated its predictive utility consistent with other HBM studies, especially that focusing on parental roles. 10,21,25,26 The HBM has proved to be an efficient tool in predicting health behaviors based on health beliefs. Consistent with other studies on dietary and health actions of parents, 21,39 in this study, perceived susceptibility, perceived severity, and cues to actions are significant predictors of health actions toward children's fast food consumption to prevent childhood obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Other HBM studies on parents' beliefs focused on children's flu vaccination; 26 HPV vaccination for children; 27 and healthy weight management among elementary school students. 10 Chomitz et al 10 found that cues to action are associated with more adoption of health behaviors.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Additional factors previously noted in the literature to be associated with vaccination coverage were also entered into the models due to their potential theoretical importance. Such factors included child age, maternal age, maternal education, presence of a personal doctor or nurse, accessibility of services and discontinuous insurance coverage [15,[30][31][32][33]. All analyses were performed using SPSS version 17.0 (SPSS Inc. Chicago, Ill).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that there was a significant improvement in the percentages all the items of OSES scale post-intervention (P= 0.000). Table ( 6) shows that there are a significant increase in the mean score of the osteoporosis self-efficacy items related to exercise practice, items related to calcium intake and total OSES score post-intervention compared to them pre it. …”
Section: Methodmentioning
confidence: 99%